Exploring Impacts of River Discharge on Forage Fish and Predators Using Ecopath With Ecosim - Sinnickson, Dylan; Chagaris, David; Allen, Micheal (Frontiers in Marine Science, 2021)
The ecology of estuaries is shaped significantly by the extent of freshwater discharge which regulates abiotic processes and influences overall biological productivity. The Suwannee River Estuary of Florida’s Big Bend Coastline has historically been a productive and diverse estuarine ecosystem supported by significant freshwater inputs from the Suwannee River. In recent years, significant changes in land use and climatic conditions have resulted in lower discharges from the Suwannee. Our objectives were to explore the impact of freshwater inputs from the Suwannee River on the estuarine forage fish and sportfish communities downstream. We built a trophic-dynamic food web model in Ecopath with Ecosim to simulate different levels of discharge and evaluate how changes in discharge (drought and floods) would influence the trophic structure of the food web. Using the fitted model, we applied a series of different short-term and long-term flow projections under different climatic scenarios to evaluate impacts on fish functional groups and sportfish biomass. Simulations suggested that ecological production was more influenced by drought conditions than flood conditions. In our short-term scenarios, the drought simulations produced biomass changes that were approximately twice as substantial as the flood scenarios. When making comparisons to other published EwE models, we generally observed smaller changes in biomass production. Although this model focused on the influence of bottom-up effects, we observed strong top-down control of snook (Centropomus undecimalis) on the system. Several functional groups were particularly sensitive to changes in snook abundance which included spotted seatrout (Cynoscion nebulosus), sand seatrout (C. arenarius), and other members of the family Sciaenidae. Because snook have recently colonized the estuary, likely as a result of warmer winter temperatures, this finding has implications for climate change and natural resource management.